2008
DOI: 10.1105/tpc.107.057190
|View full text |Cite
|
Sign up to set email alerts
|

Promoter-Proximal Introns in Arabidopsis thaliana Are Enriched in Dispersed Signals that Elevate Gene Expression  

Abstract: Introns that elevate mRNA accumulation have been found in a wide range of eukaryotes. However, not all introns affect gene expression, and direct testing is currently the only way to identify stimulatory introns. Our genome-wide analysis in Arabidopsis thaliana revealed that promoter-proximal introns as a group are compositionally distinct from distal introns and that the degree to which an individual intron matches the promoter-proximal intron profile is a strong predictor of its ability to increase expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(235 citation statements)
references
References 64 publications
13
220
2
Order By: Relevance
“…The gene expression assay demonstrated that this motif enhanced gene expression of the GmKASIIIA locus, as had been observed before in Arabidopsis (Rose et al 2008). The increases in GmFATB1b, GmFATB2a, and GmFATB2b transcripts observed in Satelite (fap nc and GmKASIIIA mutations) showed that when the transcription of the most highly transcribed GmFATB1a homolog is compromised (Wilson et al 2001b;Cardinal et al 2007), the soybean plant up regulates the transcription of the other three GmFATB genes to try to maintain a ''normal'' fatty acid biosynthesis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The gene expression assay demonstrated that this motif enhanced gene expression of the GmKASIIIA locus, as had been observed before in Arabidopsis (Rose et al 2008). The increases in GmFATB1b, GmFATB2a, and GmFATB2b transcripts observed in Satelite (fap nc and GmKASIIIA mutations) showed that when the transcription of the most highly transcribed GmFATB1a homolog is compromised (Wilson et al 2001b;Cardinal et al 2007), the soybean plant up regulates the transcription of the other three GmFATB genes to try to maintain a ''normal'' fatty acid biosynthesis.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, examination of sequencing results for Glyma09g41380 revealed a single unique polymorphism in C1726 (G174A, relative to the start codon) shown in Fig. 1, which was predicted to disrupt the donor splice site recognition between exon one and intron one (Hebsgaard et al 1996;Long and Deutsch 1999 In addition, the G to A change in C1726 creates the GATCTG motif that has been associated with enhanced gene expression when present in the first intron in Arabidopsis (Rose et al 2008).…”
Section: Mapping the Fap1 Locusmentioning
confidence: 99%
“…Several factors can affect gene expression, including gene GC content of the gene (Kudla et al, 2006), intron size (Ren et al, 2006), intron motifs (Rose et al, 2008), methylated transposon distribution (Hollister and Gaut, 2009), and chromosomal rearrangements (Marques-Bonet et al, 2004). Most notable for our study is the negative correlation between transcript level and density of recent transposon insertions that may be methylated (Hollister and Gaut, 2009).…”
Section: Expression Biases Are Correlated With Sequence Divergencementioning
confidence: 87%
“…However, transposon insertions into introns could still be deleterious as not every intron is without function. Introns can encode microRNAs (Ying and Lin, 2009), contain RNA splicing regulatory motifs (Ponthier et al, 2006), or promote intronmediated enhancement (Mascarenhas et al, 1990;Rose et al, 2008). Introns made larger by transposon insertions could affect pre-mRNA splicing and impact plant fitness, as intron size is critical for the splicing efficiency of pre-mRNA (Klinz and Gallwitz, 1985).…”
Section: Pseudogenization Event In Gm8 Gm15 and Pv5mentioning
confidence: 99%
“…Introns have been shown to influence gene expression at multiple steps along this pathway. For example, splicing has been reported to enhance mRNA transcription, 26,[34][35][36][37] promote the 39 end processing/polyadenylation, 38,39 and reduce mRNA decay. 40 Our finding that luciferase and LacZ mRNA levels were unchanged in the absence of an intron argues against a role for any one of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%